The lost stallions - Sterling Entertainment Group; United American Video (Firm) (Fort Mill, SC : Sterling Entertainment : exclusively distributed by UAV Distribution, 2003)
A coming of age story of four adventurous young friends who set out on a quest to capture four prize stallions that have broken free from a wealthy stable. Though motivated by the reward money, they come to realize their friendship is much more valuable as they face challenges on their journey.
Title from disc surface.
Special features: still gallery, bonus footage, behind the scenes featurette, director's commentary.
Parental guidance; occasional language may not be suitable for younger viewers.
DVD; stereo., Dolby digital.
Keywords: Friendship -- Drama; Feature films